Reactance and elastance as measures of small airways response to bronchodilator in asthma - Bhatawadekar, S. A.; Leary, D.; de Lange, V.; Peters, U.; Fulton, S.; Hernandez, P.; McParland, C.; Maksym, G. N. (Journal of applied physiology (1985), 2019)
Bronchodilation alters both respiratory system resistance (Rrs) and reactance (Xrs) in asthma, but how changes in Rrs and Xrs compare, and respond differently in health and asthma, in reflecting the contributions from the large and small airways has not been assessed. We assessed reversibility using spirometry and oscillometry in healthy and asthma subjects. Using a multibranch airway-tree model with the mechanics of upper airway shunt, we compared the effects of airway dilation and small airways recruitment to explain the changes in Rrs and Xrs. Bronchodilator decreased Rrs by 23.0 (19.0)% in 18 asthma subjects and by 13.5 (19.5)% in 18 healthy subjects. Estimated respiratory system elastance (Ers) decreased by 23.2 (21.4)% in asthma, with no significant decrease in healthy subjects. With the use of the model, airway recruitment of 15% across a generation of the small airways could explain the changes in Ers in asthma with no recruitment in healthy subjects. In asthma, recruitment accounted for 40% of the changes in Rrs, with the remaining explained by airway dilation of 6.8% attributable largely to the central airways. Interestingly, the same dilation magnitude explained the changes in Rrs in healthy subjects. Shunt only affected Rrs of the model. Ers was unaltered in health and unaffected by shunt in both groups. In asthma, Ers changed comparably to Rrs and could be attributed to small airways, while the change in Rrs was split between large and small airways. This implies that in asthma Ers sensed through Xrs may be a more effective measure of small airways obstruction and recruitment than Rrs. NEW & NOTEWORTHY This is the first study to quantify to relative contributions of small and large airways to bronchodilator response in healthy subjects and patients with asthma. The response of the central airways to bronchodilator was similar in magnitude in both study groups, whereas the response of the small airways was significant among patients with asthma. These results suggest that low-frequency reactance and derived elastance are both sensitive measures of small airway function in asthma.